EU: European Parliament adopts ban on facial recognition but leaves migrants, refugees and asylum seekers at risk - Amnesty International (Amnesty International, 2023)
EU: European Parliament adopts ban on facial recognition but leaves migrants, refugees and asylum seekers at risk. Responding to the European Parliament’s decision to ban invasive mass surveillance technologies in its Artificial Intelligence Act (AI Act), Mher Hakobyan, Advocacy Advisor on AI Regulation said: “We welcome the European Parliament’s decision to adopt a ban on abusive mass surveillance technology in today’s landmark vote. However, it is essential the Parliament and EU Member States ensure that development, sale, use and export of facial recognition and other mass surveillance technologies are banned in the final AI Act during upcoming negotiations.
Keywords: 2023-06 June